The effect of the strategy Observe - reverse - explain in the acquisition of historical concepts for students of the literary fifth grade in the subject of history (Journal of the College of Basic Education, 2022)
The study research aims to identify (after the effect of the use in the acquisition of Progressive depth historical perceptions of fifth-grade students in the literary material style historic To achieve this, the researcher chose the experimentally determined a partial seizure students by Pilot and the other officer with a post-test and chose the researcher randomly fifth grade literary students in the High School Farabi for Boys where he formed the sample of 60 students by 30 students in the experimental group that teaches its students according to the style of the Progressive depth and 30 students in the control group where he taught students according to ordinary method The Cava researcher between the two sets of research in a number of variables are (chronological age of the students measured in Months, and degrees of the previous achievement in history, and a variable IQ) were then determine the scientific article, which included chapters four recent book of modern and contemporary history of fifth grade literary, and coined the researcher targets behavioral relied on Bloom's Taxonomy of the six levels (knowledge, understanding, application, analysis, installation, Calendar) has reached the number is (126) target, as a promising set of lesson plans for the topics in history, and in line with the objective of this research promising researchers test the acquisition of historical concepts of a kind multiple choice be the ultimate picture of (45) items it has been verified apparent sincerity viewing on a group of arbitrators and specialists in teaching methods and curricula have been extracted difficulty and power plants discriminatory for paragraphs as well as the extent of the effectiveness of alternatives and extracted test the stability of retail midterm manner and corrected equation Pearson and then Spearman Brown formula, and at the end of the experiment the test on the students of the two sets of search dish and adopted Altaia test binocular independent data processing statistically as results showed superiority of the experimental group that studied manner Progressive depth to the control group, who studied in the usual way to test the acquisition of historical concepts, and in the light of this, the researcher recommended using the style of Progressive delve deeper into the teaching of history